Assessment Of Ground Deformations Using Insar Techniques And Shallow Subsurface Imaging In Pulau Pinang, Malaysia - Olukunle, Rauff Kazeem (2021)
Ground deformation presents a significant threat to people's lives and properties in Pulau Pinang, Malaysia. It usually occurs when there is continuous heavy rainfall. Previous methods on this hazard were based on simulation, modelling, and geo-engineering issues. Still, none of them quantified the movements using the Interferometric Synthetic Aperture Radar (InSAR) technique. In this research, a combination of InSAR and geophysical techniques is introduced to assess the potential hazard zones and the possible causes in Pulau Pinang. This region was chosen for this research as it has high reflectivity and ground displacement potential. Permanent Scatterer- InSAR (PS-InSAR) and Small Baseline Subset- InSAR (SBAS-InSAR) techniques were used to monitor, quantify, and map the region’s deformations. Sixty ascending and fifty-six descending Sentinel-1A (S-1A) datasets obtained between 2016 and 2019 and nineteen descending ENVISAT ASAR acquired from 2003 to 2010 were processed and analysed. Electrical Resistivity (ER) and Ground Penetrating Radar (GPR) surveys were conducted at some selected sites based on InSAR deformation maps' results.